Landscape analysis for the American crocodile Crocodylus acutus (Reptilia: Crocodilidae) in northwestern Costa Rica - Sandoval Hernández, Iván (2022)
Northwest Costa Rica has the largest crocodile population in the country, but it is also an important area of the human population growth, tourism, crops, and aquaculture, that have generated great changes in the region. For these reasons, a landscape analysis for the American crocodile, Crocodylus acutus, was conducted to determine which landscape variables may benefit the reptile. The analysis included the Tempisque Great Wetlands (TGW) and the Central Pacific (CP). The TGW had a higher linear density of rivers and roads, and more extensive wetlands and flood zones, whereas the CP had a higher number of towns. Forest coverage was recovering in both regions, although the rate of recovery was different. The values of the fractal dimension (FD), the shape index (SI), the Shannon diversity index, and the equity index increased slightly in both zones, indicating that fragmentation is increasing in the study area. The average density of crocodiles was correlated with change in coverage per year (rs = 0.74) and with FD and SI (rs = 0.65 for both). In the CP, the density of crocodiles was also correlated with change in coverage per year (rs = 0.48) and with FD and SI (rs = 0.93 and 0.74, respectively).